Bioaccumulation, oxidative stress, immune disruption, and metabolic alterations in Mytilus galloprovincialis exposed to nano-copper oxide - Yitong Gong; Yang Lin; Ziyan Lang; Jiawan Lv; Jing Sun; Liming Wang; Shujun Li; Weiang Zhang; Xiaoli Liu; Liping You (Marine Pollution Bulletin, 2026)

N-glycan signatures of immunoglobulins-depleted serum proteins in colorectal cancer - Huiai Lu; Yuanyuan Liu; Yi Wang; Jiajing Lin; Liming Cheng; Xin Liu; Si Liu; at (Glycoconjugate Journal, 2026)

Sixteen-year dynamics of heavy metal(loid) pollution in agricultural soils of Zhejiang Province, China: Quantifying the contest between anthropogenic pressures and environmental investments - Weiwei Wang; Zhihui Fu; Linyan Xu; Jun Hu; Xiaozeng Miao; Liming Duan; Lingwen Wang; Yun Xia; Xiaohui Sun; Daohui Lin; Zhou Shi; Kun Yang (Journal of Hazardous Materials, 2026)

Microplastic release from flexible food packaging: Effects of simulants and package structure - Zhixin Zhu; Zhaokai Zhu; Danwei Chen; Ziqing Jiang; Qiaoxin Lin; Liming Cao (Journal of Hazardous Materials, 2026)

Storm sequences reduce the wave attenuation capacity of salt marshes - Yuxi Ma; Wenzhen Zhao; Liming Xue; Bas Hofland; Lin Su; Lv Gong; Shiwei Lin; Zhan Hu; Xiuzhen Li; Tjeerd J. Bouma (Estuarine, Coastal and Shelf Science, 2026)

Retraction Note: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2026)

Multi-scale pore network approaches for predicting collector efficiency of colloids across a wide density range in soil hydrologic systems - Dantong Lin; Scott Alan Bradford; Yazhou Cao; Minpeng Tang; Baoqing Zhang; Liming Hu (Advances in Water Resources, 2026)

Mycorrhizal-association type mediates soil priming effect and its response to nitrogen addition in subtropical plantations - Wei Zhang; Xiao-Hong Wang; Liming Yin; Maokui Lyu; Lin-Qiao Jia; Li-Li Wang; Ai-Ping Liu; Xiao-Die Hu; Xiaodong Yao; Guang-Shui Chen (Pedobiologia, 2026)

A graph-based C-BOM framework integrating multi-view xBOM data for efficient product carbon footprint assessment - Weitong Liu; Liming Wang; Fangyi Li; Lin Kong; Xingyuan Xiao; Yitong Wang; Yuqi Cui; Boyun Wang; Liuyuan Li (Journal of Cleaner Production, 2026)

System dynamics: A new method for evaluating the low-carbon effects of underground space development capacity forecasts in rail transit hub station areas - Chunxiang Lin; Liming Wu; Haishan Xia; Penglin Li; Xiaodan Chen; Canghui Zhu; Lianjie Jin; Xiangjun Sun (Sustainable Cities and Society, 2026)

Sustainable multifunctional packaging films based on chitosan and food waste-derived carbon nanodots for fruit preservation - Ying Ren; Dan Chen; Shiyu Lin; Xiaoping Fan; Liming Cao (Journal of Food Engineering, 2026)

A coordination-covalent dual-network enables weak gradient-strong response in PVA-based bilayer humidity actuator - Qiaoxin Lin; Ziqing Jiang; Zhixin Zhu; Liming Cao (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Concomitant exposure to residential greenness, nitrogen dioxide, and outdoor light at night in association with incident anxiety - Jiayun Zhang; Yexiang Sun; Zihan Li; Lisha Xu; Jingjing Hu; Jie Qiu; Xinhan Zhang; Zongming Yang; Zhanghang Zhu; Yonghao Wu; Yixing Wang; Hongbo Lin; et al. (Landscape and Urban Planning, 2026)

Active faulting and crustal deformation along the East Sunda-Banda Arc: Implications for Regional Geohazards - Xiaodong Yang; Xiwu Luan; Liangyu Zhu; Xinze Han; Zhiwen Zhang; Zhiyuan Zhou; Jian Lin; Liming Wang (Global and Planetary Change, 2026)

Contrasting fine root-induced rhizosphere priming effects between coniferous and broadleaved trees - Weijun Zhang; Junjie Lin; Qitai Cheng; Liming Yin; Wenling Zhang; Amit Kumar; Xiali Mao; Hongxin Dong; Dafeng Hui; Mengguang Han; Lei Tao; Dingxin Su; et al. (Biology and Fertility of Soils, 2026)

An end-to-end reactive oxygen species scavenger for targeted therapy of myocardial ischemia-reperfusion injury by concurrently eliminating superoxide anion and hydroxyl radical - Shuya Wang; Yuting Lin; Tianjiao Zhao; Xiaojing Shi; Tingli Xiong; Ruishi Li; Wenxuan Zheng; Min Liu; Fei Li; Jiawen Wei; Ling Yang; Qiong Huang; et al. (Chemical Engineering Journal, 2026)

Research on the adsorption mechanism of CH4, CO2 and N2 in micropores of high-rank coal and the determinants of adsorbed amount: Insight of molecular modeling - Qiang Liu; Dazhao Song; Liming Qiu; Anhu Wang; Yujie Peng; Yi Zhu; Lin Liu (Fuel, 2026)

Associations of concomitant exposure to outdoor light at night, air pollution, and greenness with metabolic syndrome: A cohort study in China - Lisha Xu; Yexiang Sun; Zihan Li; Jiayun Zhang; Yichao Dai; Ye Jiao; Zhanghang Zhu; Jingjing Hu; Jie Qiu; Yixing Wang; Hongbo Lin; Liming Shui; et al. (Environmental Research, 2026)

Differences in priming effect of topsoil versus subsoil depends on ecosystem type - Lei Tao; Liming Yin; Feike A. Dijkstra; Junjie Lin; Peng Wang; Weixin Cheng (CATENA, 2026)

Walkability, fine particulate matter and risk of Osteoporosis: A cohort study in China - Jie Qiu; Peng Shen; Jingjing Hu; Zhanghang Zhu; Lisha Xu; Jiayun Zhang; Zihan Li; Hongbo Lin; Liming Shui; Feng Tong; Kun Chen; Jianbing Wang (Atmospheric Environment, 2026)

Identification of Mitochondria-Related Genes Associated with Stroke Risk Through Multi-omics Summary Data-Based MR Analysis - Xiaorong Tang; Guannan Cheng; Siyun Chen; Lulu Yao; Liming Lu; Chenwei Shen; Lubao Feng; Wenwen Zhang; Nenggui Xu; Lin Wang (Molecular Neurobiology, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

Breaking the limitations of scenes and sensors variability: A novel unsupervised domain adaptive instance segmentation framework for agricultural field extraction - Ren Wei; Lin Yang; Xiang Li; Chenxu Zhu; Lei Zhang; Jie Wang; Jie Liu; Liming Zhu; Chenghu Zhou (Remote Sensing of Environment, 2025)

Bio-templated nanocellulose/ZnO hybrids reinforced PVA/chitosan films with synergistic antibacterial activity for enhanced food preservation - Dan Chen; Shiyu Lin; Liming Cao; Wei Huang (Food Packaging and Shelf Life, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Enzymatic hydrolysis of cassava leaf proteins unlocks antioxidant and therapeutic peptides: Alcalase-derived bioactives target oxidative stress pathways - Jinquan Zhang; Yusi Fang; Zuoda Zhang; Houmei Yu; Liming Lin; Qinfei Wang; Zhenwen Zhang; Yong Song (Food Chemistry, 2025)

Combined non-volatile and volatile metabolite profiles and antioxidant activities reveal the enhancement of traditional “steaming and Sun-drying nine times” on the functional properties of jujube - Yu Liu; Lijuan Zhang; Haijiao Lin; Zengyi Song; Pu Xu; Liming Zhang; Binbin Wei (Food Chemistry, 2025)

A finite-volume based physics-informed Fourier neural operator network for parametric learning of subsurface flow - Xia Yan; Jingqi Lin; Yafeng Ju; Qi Zhang; Zhao Zhang; Liming Zhang; Jun Yao; Kai Zhang (Advances in Water Resources, 2025)

Residential green space and transition trajectory of cardiometabolic multimorbidity in two prospective cohorts - Yonghao Wu; Jiacheng Ying; Yexiang Sun; Lisha Xu; Zihan Li; Jiayun Zhang; Jie Qiu; Yixing Wang; Jingjing Hu; Peng Shen; Hongbo Lin; Liming Shui; et al. (Urban Forestry & Urban Greening, 2025)

Protective effects of quercetin on LPS-induced liver injury in quails - Xinran Li; Shuang Yang; Lingxin Zhu; Huanni Song; Liming Lin; Changyu Cao (Toxicon, 2025)

Investigation of transport and deposition behavior and mechanisms of micro-nano-bubbles in porous media - Yazhou Cao; Dantong Lin; Zhen-Yu Yin; Liming Hu (Journal of Hydrology, 2025)

Biological age acceleration mediates effects of household air pollution from solid fuels on dementia risk: A prospective cohort study in China - Haisheng Wu; Zengxian Lin; Chunren Zhang; Yuxing Jiang; Liming Bai; Jiazhen Zheng; Suosu Wei; Chunxia Deng (Environmental Pollution, 2025)

Correction: Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)

Long non-coding RNA MINCR silencing contributes to suppressed gemcitabine resistance in bladder cancer by blocking the ZEB1/PHGDH axis through microRNA-876-5p up-regulation - Linfei Xu; Yongfeng Lin; Liming Zhang; Xingzhang Lin; Sheng Liu (Journal of Molecular Histology, 2025)

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Thermal-enhanced deep removal of multiple impurities upon pH induction towards selective regeneration of high-purity iron phosphate - Yaohui Xie; Fen Zhang; Shuyu Xiang; Guang Yang; Lin Qu; Fei Han; Liang Xu; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2025)

Incorporation of probiotics with pressure-sensitive pectin-fructooligosaccharide hydrogel for potential intestinal delivery - Mengwen Duan; Liming Che; Xuee Wu; Siew Young Quek; Bangzhou Zhang; Hao Lin; Ning He (Carbohydrate Polymers, 2025)

Letter to the editor: Comments on “Microplastic polyethylene induced inner ear dysfunction in murine model” - Haonan Lin; Liming Shang; Lexin Wang; Ke Xu (Journal of Hazardous Materials, 2025)

Giant diatom blooms driven by deep water upwelling since late MIS3? Evidence from the rim of the Mariana Trench - Junyu Lin; Dong Xu; Yue Li; Liming Ye; Qian Ge; Yeping Bian; Xibin Han; Weiyan Zhang; Shenghui Cheng (Frontiers in Marine Science, 2025)
Laminated Diatom Mats (LDMs) in the low-latitude Western Pacific provide key insights into global climate and carbon cycling. While Ethmodiscus rex ( E. rex ) LDMs research has advanced, two critical aspects remain to be elucidated: (1) the precise chronology of LDMs formation, and (2) its relationship with oceanic circulation patterns and associated nutrient flux variations. In this study, we employed AMS 14 C dating coupled with carbonate content variations to constrain the formation age of LDMs, complemented by comprehensive geochemical and clay mineral analyses of core E20, we found: (1) Diatom blooms occurred mainly from Last Glacial Maximum (LGM) to early Holocene; (2) Sediments are mostly volcanic, with increased material in E. rex layers suggesting stronger deep currents transported volcanic debris; (3) Blooms weren’t solely caused by Asian dust-derived nutrients. We propose deep current intensification and topographic upwelling drove diatom growth, highlighting deep ocean processes’ role in surface productivity and LDMs formation. This advances understanding of their climate and carbon cycle significance.

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

Association of residential greenness and sleep duration in adults: A prospective cohort study in China - Jiayi Li; Yaoyao Lin; Zongming Yang; Joachim Heinrich; Tianyu Zhao; Zhebin Yu; Wenqing Wang; Kaixuan Yang; Peng Shen; Hongbo Lin; Liming Shui; Jianbing Wang; et al. (Environmental Research, 2025)

Microglia Promote Lymphangiogenesis Around the Spinal Cord Through VEGF-C/VEGFR3-Dependent Autophagy and Polarization After Acute Spinal Cord Injury - Yeyang Xian; Jie Liu; Mengxuan Dai; Wensheng Zhang; Minye He; Zhengnong Wei; Yutao Jiang; Shiyong Le; Zhuoang Lin; Shuai Tang; Yunfei Zhou; Liming Dong; et al. (Molecular Neurobiology, 2025)

Production and evaluation of a bivalent adjuvant inactivated vaccine against infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus - Zhen Zhang; Chunyan Guan; Jingzhuang Zhao; Jingnan Lin; Yizhi Shao; Linfang Li; Tongyan Lu; Peng Chen; Yong-An Zhang; Liming Xu (Aquaculture, 2025)

Preparation of emulsion-template oleogels: Tuning properties by controlling initial water content and evaporation method - Wenbo Miao; Zhiheng Zhang; Qianzhu Lin; David Julian McClements; Hangyan Ji; Liming Jiang; Jinsheng Wen; Zhengyu Jin; Chao Qiu (Food Hydrocolloids, 2025)

The importance of porewater exchange process on carbon lateral export from saltmarsh creek to coastal sea - Jian’an Liu; Xueqing Yu; Xinyi Lin; Tong Peng; Liming Xue; Jinzhou Du (Journal of Oceanology and Limnology, 2025)

Recent advances in natural gums as additives to help the construction and application of edible biopolymer gels: the example of hydrogels and oleogels - Wenbo Miao; Han Jiang; Xiaojing Li; Shangyuan Sang; Liming Jiang; Qianzhu Lin; Zhiheng Zhang; Long Chen; Jie Long; Aiquan Jiao; Jinpeng Wang; Zhengyu Jin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

A metabolic roadmap of waxy corn flavor - Jingyun Luo; Chunmei He; Shijuan Yan; Chenglin Jiang; An Chen; Kun Li; Yongli Zhu; Songtao Gui; Ning Yang; Yingjie Xiao; Shenshen Wu; Fajun Zhang; et al. (Molecular Plant, 2024)

Physical modeling of organics-contaminated groundwater remediation by ozone micro-nano-bubbles enhanced oxidation - Liming Hu; Yazhou Cao; Zhiran Xia; Dantong Lin (Journal of Hydrology, 2024)

Association of fine particulate matter and residential green space with rheumatoid arthritis - Jingjing Hu; Peng Shen; Yingying Mao; Jie Qiu; Lisha Xu; Yonghao Wu; Yixing Wang; Ye Ding; Hongbo Lin; Liming Shui; Tong Feng; Jianbing Wang; et al. (Environmental Research, 2024)

Outdoor light at night, air pollution and risk of incident type 2 diabetes - Yonghao Wu; Ye Jiao; Peng Shen; Jie Qiu; Yixing Wang; Lisha Xu; Jingjing Hu; Jiayun Zhang; Zihan Li; Hongbo Lin; Zhiqin Jiang; Liming Shui; et al. (Environmental Research, 2024)

Macrophage activation syndrome in Sepsis: from pathogenesis to clinical management - Shunyao Chen; Cong Zhang; Jialiu Luo; Zhiqiang Lin; Teding Chang; Liming Dong; Deng Chen; Zhao-Hui Tang (Inflammation Research, 2024)

Direct recovery of high-purity lithium via nanofiltration membranes from leaching solution of spent lithium batteries - Shiweihua He; Qiuyang Zuo; Hui Shi; Zhiwei Geng; Congcong Liu; Lin Ding; Xin Li; Penghui Shao; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2024)

Functionality developments in montmorillonite nanosheet: Properties, preparation, and applications - Wei Wang; Liming Wu; Lin Chang; Wenshuai Yang; Liang Si; Hongyan Nan; Weijun Peng; Yijun Cao (Chemical Engineering Journal, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Construction of oleogels based on emulsion gels stabilized by glycyrrhizic acid and chitosan - Qianzhu Lin; Chenxi Wang; Zhengyu Jin; Liming Jiang; Jinsheng Wen; David Julian McClements; Chao Qiu (Food Hydrocolloids, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Spatial–temporal distribution characteristics of surface water pollutants and their potential sources in Ngari, China - Yubing Zhu; Xiao Sun; Lin Shi; Di Zhang; Meizhen Wu; Liming Chai; Jinfeng Zhao (Environmental Geochemistry and Health, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Corrigendum to “The effect of postharvest water migration on metabolism of cassava root by hypobaric storage” [Innovative Food Science and Emerging Technologies, 93 (May 2024)103609] - Liming Lin; Xiuqin Luo; Houmei Yu; Qinfei Wang; Zhenwen Zhang; Kaimian Li (Innovative Food Science & Emerging Technologies, 2024)

Genome-wide CRISPR screening identifies critical role of phosphatase and tensin homologous (PTEN) in sensitivity of acute myeloid leukemia to chemotherapy - Liming Lin; Jingjing Tao; Ying Meng; Yichao Gan; Xin He; Shu Li; Jiawei Zhang; Feiqiong Gao; Dijia Xin; Luyao Wang; Yili Fan; Boxiao Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

CO2 mineralization and utilization by tailings sand in China for potential carbon sinks and spatial project layout - Huaqing Li; Yahui Bian; Mingliang Liu; Jianyi Lin; Min Dai; Hongyi Xie; Huajun Yu; Bin Chen; Meili Xue; Zhiwei Li; Jingjing Yin; Liming Xue (Resources, Conservation and Recycling, 2024)

Narrow bandgap Sn-Pb perovskite solar cells with high operational stability modulated by imidazoline derivative - Feilin Zou; Chenghao Duan; Zhuojia Lin; Zheng Zhang; Shuang Xu; Chang Chen; Jianwei Chen; Jiong Li; Shibing Zou; Liming Ding; Hongze Luo; Keyou Yan (Chemical Engineering Journal, 2024)

Coupling of source rock gas expulsion intensity and reservoir quality in time and space-a key to determine gas accumulation in Upper Paleozoic tight sandstones of the Mugua gas field, Ordos Basin, China - Ziyi Wang; Shuangfang Lu; Nengwu Zhou; Yancheng Liu; Liming Lin; Yaxin Shang (Marine and Petroleum Geology, 2024)

Fabrication and characterization of emulsion-template oleogels assembled from octenyl succinic anhydride starch/chitosan electrostatic complexes - Wenbo Miao; David Julian McClements; Zhiheng Zhang; Qianzhu Lin; Hangyan Ji; Jinpeng Wang; Zhengyu Jin; Guanghua Li; Liming Jiang; Jinsheng Wen; Shangyuan Sang; Chao Qiu (Food Hydrocolloids, 2024)

A pioneering study on EDOT recovery from the PEDOT wastewater: Integration of COSMO-SAC prediction, experiment, and process simulation - Yin Zhu; Zhikai Cao; Liming Che; Haiqiang Lin; Quancong Zhang; Hua Zhou (Journal of Cleaner Production, 2024)

The effect of postharvest water migration on metabolism of cassava root by hypobaric storage - Liming Lin; Xiuqin Luo; Houmei Yu; Qinfei Wang; Zhenwen Zhang; Kaimian Li (Innovative Food Science & Emerging Technologies, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

CDC-like kinase 3 deficiency aggravates hypoxia-induced cardiomyocyte apoptosis through AKT signaling pathway - Xiue Ma; Liming Gao; Rucun Ge; Tianyou Yuan; Bowen Lin; Lixiao Zhen (In Vitro Cellular & Developmental Biology - Animal, 2024)

Effect of trigger system on experimental dispersion characteristics of active surface wave testing - Shibin Lin; Jeramy C. Ashlock; Liming Zhu; Zexiang Qin; Bo Li; Xingji Zhu; Changhai Zhai (Earthquake Engineering and Engineering Vibration, 2024)

High-performance triboelectric nanogenerators based on blade-coating lead halide perovskite film and electrospinning PVDF/graphene nanofiber - Yong Jiao; Zhenhua Lin; Xintong Ma; Long Zhou; Xing Guo; Zhaosheng Hu; Xian-gang Hu; Xue Zhao; Liming Ding; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Metagenomic insights into protein degradation mechanisms in natural fermentation of cassava leaves - Jinquan Zhang; Qinfei Wang; Houmei Yu; Liming Lin; Zhenwen Zhang; Yong Song (Bioresource Technology, 2024)

Prognostic significance and immune escape implication of tumor-infiltrating neutrophil plasticity in human head and neck squamous cell carcinoma - Xiaoke Zhu; Yu Heng; Duo Zhang; Di Tang; Jian Zhou; Hanqing Lin; Jingyu Ma; Xuping Ding; Lei Tao; Liming Lu (Human Cell, 2024)

The Influence of Seamounts on the Enrichment of Rare Earth Elements in Sediments—A Case Study of the Marcus-Wake Seamounts in the Western Pacific Ocean - Tinglu Xiao; Dong Xu; Tao Deng; Junyu Lin; Liming Ye; Qian Ge; Xibin Han; Yanhui Dong; Fengyou Chu (Journal of Marine Science and Engineering, 2024)
Deep-sea sediments enriched in rare earth elements and yttrium (REY-rich sediments) are widely distributed on the deep-sea floor, and their formation mechanism remains elusive. Although studies have recognized the link between seamounts and REY-rich sediments, in-depth analysis of the specific roles and effects of seamounts in the formation of REY-rich sediments is lacking. In this study, we analyzed surface sediments from the Marcus-Wake Seamounts for grain size, geochemistry, and mineral composition and classified the samples into three types: samples with moderate REY content and dominated by terrestrial detritus; samples with high REY and authigenic mineral content; and samples rich in CaCO3 but poor in REY. The REY in the sediments of the study area partly originate from Asian dust input and partly from seawater and/or pore water, and are mainly enriched in REY carrier particles including bioapatite fossils and micronodules. The amount of REY carrier particles influences the REY content in the sediments. The current field, primary productivity, weathering process, and depositional environment around seamounts are different from those of abyssal plains, which are conducive to the formation of REY-rich sediments. Strong bottom currents may exist in the southeastern direction of some large seamounts (e.g., Niulang Guyot), leading to the selective accumulation of REY-rich bioapatite fossils and micronodules, resulting in the formation of REY-rich sediments.

Towards efficient and accurate CO2 sequestration optimization: Integrating hierarchical spatio-temporal information into deep-learning-based surrogate models - Jingqi Lin; Kai Zhang; Liming Zhang; Piyang Liu; Wenfeng Peng; Huaqing Zhang; Xia Yan; Chen Liu; Yongfei Yang; Hai Sun; Jun Yao (Fuel, 2024)

Diagenesis as a control on the tight sandstone reservoir quality of the upper Carboniferous strata in the northeastern Ordos basin, China - Ziyi Wang; Shuangfang Lu; Nengwu Zhou; Yancheng Liu; Liming Lin; Yaxin Shang; Guangshun Xiao; Jun Wang (Marine and Petroleum Geology, 2023)

Mapping trade-offs among key ecosystem functions in tidal marsh to inform spatial management policy for exotic Spartina alterniflora - Wenzhen Zhao; Xiuzhen Li; Liming Xue; Shiwei Lin; Yuxi Ma; Lin Su; Zeyuan Li; Lv Gong; Zhongzheng Yan; Peter I. Macreadie (Journal of Environmental Management, 2023)

An electroconductive hydrogel with injectable and self-healing properties accelerates peripheral nerve regeneration and motor functional recovery - Zhenwei Yi; Fangke Zhan; Yijia Chen; Ran Zhang; Haodong Lin; Liming Zhao (Chemical Engineering Journal, 2023)

Targeted Metabolomic Analysis of the Eye Tissue of Triple Transgenic Alzheimer’s Disease Mice at an Early Pathological Stage - Liming Shen; Xiaoxiao Tang; Huajie Zhang; Hongbin Zhuang; Jing Lin; Yuxi Zhao; Xukun Liu (Molecular Neurobiology, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

A Systematic Investigation of Complement and Coagulation-Related Protein in Autism Spectrum Disorder Using Multiple Reaction Monitoring Technology - Xueshan Cao; Xiaoxiao Tang; Chengyun Feng; Jing Lin; Huajie Zhang; Qiong Liu; Qihong Zheng; Hongbin Zhuang; Xukun Liu; Haiying Li; Naseer Ullah Khan; Liming Shen (Neuroscience Bulletin, 2023)

Generation, accumulation, and distribution of Upper Paleozoic tight sandstone gas in the northeastern margin of the Ordos Basin - Ziyi Wang; Nengwu Zhou; Shuangfang Lu; Yancheng Liu; Liming Lin; Yang Liu; Bo Song (Marine and Petroleum Geology, 2023)

Decomplexation of Ni-EDTA enhanced by Fe(III) reduction in the Fenton reaction: Insight into the role of carbonyl groups - Meiling Chen; Lin Ding; Shijun Zhu; Xiuqin Xiong; Xinkai Yuan; Yanhua Peng; Liming Yang; Hui Shi; Penghui Shao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2023)

Study on the Mechanism of Arsenic-Induced Lung Injury Based on SWATH Proteomics Technology - Yi Wang; Jun Zhang; Xinglai Zhang; Huajie Zhang; Xueshan Cao; Ting Hu; Jing Lin; Xiaoxiao Tang; Xiaolu Chen; Yuxuan Jiang; Xi Yan; Hongbin Zhuang; et al. (Biological Trace Element Research, 2023)

Residential greenness, air pollution and incident neurodegenerative disease: A cohort study in China - Zhanghang Zhu; Zongming Yang; Luhua Yu; Lisha Xu; Yonghao Wu; Xinhan Zhang; Peng Shen; Hongbo Lin; Liming Shui; Mengling Tang; Mingjuan Jin; Jianbing Wang; et al. (Science of The Total Environment, 2023)

Highly effective recovery of palladium from a spent catalyst by an acid- and oxidation-resistant electrospun fibers as a sorbent - Nianshou Cheng; Lin Zhang; Mingyue Wang; Jiancheng Shu; Penghui Shao; Liming Yang; Xiaojing Meng; Yuzhu Fan; Min Li (Chemical Engineering Journal, 2023)

Expression profiles of the CD274 and PLEKHH2 gene and association of its polymorphism with hematologic parameters in sheep - Yukun Zhang; Xiaoxue Zhang; Fadi Li; Changchun Lin; Deyin Zhang; Benzhen Duan; Yuan Zhao; Xiaolong Li; Dan Xu; Jiangbo Cheng; Liming Zhao; Jianghui Wang; et al. (Veterinary Immunology and Immunopathology, 2023)

Mud cracks promote colonization by pioneer saltmarsh plants - Can Jiang; Xiuzhen Li; Wenzhen Zhao; Liming Xue; Lin Su (Frontiers in Marine Science, 2023)
Saltmarshes are valued as key buffering ecosystems against global climate change and sea level rise. However, the knowledge deficit regarding links between colonization of saltmarsh fringes by plants and mud cracking in the lateral dimension considerably limits our understanding of marsh resilience. Here, the role of mud cracks in colonization by saltmarsh plants was investigated. A combination of field experiments, remote sensing, and experimental results revealed that: (1) potential mud cracking zones were formed at the seaward edge of saltmarshes under the influence of tide-induced wetting–drying cycles, where mud cracks were extensively distributed and colonized by new seedlings. (2) The seedling density in the mud cracks was higher than that in the patches, and seedlings in the mud cracks sprouted earlier than those in the patches. The results implied that mud cracking enhanced colonization by saltmarsh plants, rather than being a water stressor. (3) The two main ecological functions of mud cracks in saltmarsh colonization were acting as “seed traps” and “seedling growth promoters.” (4) Mud cracking could be a key factor influencing saltmarsh resilience, especially by promoting the colonization and dispersal of saltmarsh plants. Rapid colonization of potential zones with mud cracks could occur as soon as seeds are available. Our results could facilitate the development of appropriate saltmarsh rehabilitation strategies.

Wave attenuation by flattened vegetation (Scirpus mariqueter) - Yuxi Ma; Longhuan Zhu; Zhong Peng; Liming Xue; Wenzhen Zhao; Tianyou Li; Shiwei Lin; Tjeerd J. Bouma; Bas Hofland; Chuning Dong; Xiuzhen Li (Frontiers in Marine Science, 2023)
With the capacity to reduce wave energy and trap sediment, Scirpus mariqueter has become an important native species of annual grass for ecology restoration at the Yangtze Estuary in eastern China. Due to seasonal variances of biophysical characteristics, S. mariqueter usually bends and breaks in winter, resulting in flattened stems that may reduce its wave attenuation capacity. To investigate the effects of vegetation flattening on wave attenuation, a set of flume experiments were conducted for flattened and standing vegetation under different wave conditions. The model vegetation was designed to represent the wilted S. mariqueter collected in winter with dynamic similarity. Results showed that the wave damping coefficient for flattened vegetation ( β F ) was 33.6%-72.4% of that for standing vegetation ( β S ) with the same vegetation length. Both β F and β S increased with wave height but decreased with water depth. A wave attenuation indicator ( WAI ) was defined to generate empirical formulas for β S and β F as well as their ratio β F /β S . The empirical formulas were then applied to modify the existing standing vegetation-based wave attenuation model for flattened vegetation and performed successfully. Understanding the wave attenuation characteristics of flattened vegetation is essential for the management of ecological restoration and coastal protection.

Kainic acid induced hyperexcitability in thalamic reticular nucleus that initiates an inflammatory response through the HMGB1/TLR4 pathway - Dongbin Li; Xiaosi Zhang; Ruoshi Liu; Meixin Long; Shanshan Zhou; Jinghan Lin; Liming Zhang (NeuroToxicology, 2023)

Association of walkability and fine particulate matter with chronic obstructive pulmonary disease: A cohort study in China - Yonghao Wu; Peng Shen; Zongming Yang; Luhua Yu; Zhanghang Zhu; Tiezheng Li; Lisha Xu; Dan Luo; Xuecheng Yao; Xinhan Zhang; Lin Meng; Hongbo Lin; et al. (Science of The Total Environment, 2023)

Soy protein isolate-catechin non-covalent and covalent complexes: Focus on structure, aggregation, stability and in vitro digestion characteristics - Shicheng Dai; Peilong Liao; Yilun Wang; Tian Tian; Xiaohong Tong; Bo Lyu; Lin Cheng; Liming Miao; Weijie Qi; Lianzhou Jiang; Huan Wang (Food Hydrocolloids, 2023)

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

Trace Element Changes in the Plasma of Autism Spectrum Disorder Children and the Positive Correlation Between Chromium and Vanadium - Jun Zhang; Jing Lin; Xiying Zhao; Fang Yao; Chengyun Feng; Zhijun He; Xueshan Cao; Yan Gao; Naseer Ullah Khan; Margy Chen; Peng Luo; Liming Shen (Biological Trace Element Research, 2022)

Plant community-mediated effects of grazing on plant diseases - Tserang Donko Mipam; Fei Chen; Liming Tian; Pei Zhang; Mengjiao Huang; Lifan Chen; Xingxing Wang; Peng Zhang; Ziyuan Lin; Xiang Liu (Oecologia, 2022)

A Combined Proteomics and Metabolomics Profiling to Investigate the Genetic Heterogeneity of Autistic Children - Liming Shen; Huajie Zhang; Jing Lin; Yan Gao; Margy Chen; Naseer Ullah Khan; Xiaoxiao Tang; Qi Hong; Chengyun Feng; Yuxi Zhao; Xueshan Cao (Molecular Neurobiology, 2022)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Evaluation and improvement of the greenness of plasma spraying through life cycle assessment and grey relational analysis - Jing Liu; Liming Wang; Fangyi Li; Yanle Li; Xueju Ran; Lin Kong; Yan Fu (The International Journal of Life Cycle Assessment, 2021)

Spatial-temporal characteristics of urban air pollution in 337 Chinese cities and their influencing factors - De Zhou; Zhulu Lin; Liming Liu; Jialing Qi (Environmental Science and Pollution Research, 2021)

Enhancement of sludge dewaterability by a magnetic field combined with coagulation/flocculation: a comparative study on municipal and citric acid–processing waste-activated sludge - Ning Ding; Xiao Wang; Lin Jiang; Jianxin Zhang; Yue Geng; Liming Dong; Hong Liu (Environmental Science and Pollution Research, 2021)

Correction to: Shared genetic architecture between metabolic traits and Alzheimer’s disease: a large-scale genome-wide cross-trait analysis - Zhaozhong Zhu; Yifei Lin; Xihao Li; Jane A. Driver; Liming Liang (Human Genetics, 2021)

Effects of intercropping accumulator plants and applying their straw on the growth and cadmium accumulation of Brassica chinensis L. - Yi Tang; Liming Wang; Yongdong Xie; Xuena Yu; LiJin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2020)

Comprehensive transcriptomics and proteomics analyses of rice stripe virus-resistant transgenic rice - Yang Xu; Lvjie Bi; Zipeng Yu; Chao Lin; Liming Gan; Lifei Zhu; Haiyang Li; Yunzhi Song; Changxiang Zhu (Journal of Biosciences, 2019)

Intestinal Methylation and Demethylation of Mercury - Hong Li; Xiaoying Lin; Jiating Zhao; Liwei Cui; Liming Wang; Yuxi Gao; Bai Li; Chunying Chen; Yu-Feng Li (Bulletin of Environmental Contamination and Toxicology, 2019)

Shared genetic architecture between metabolic traits and Alzheimer’s disease: a large-scale genome-wide cross-trait analysis - Zhaozhong Zhu; Yifei Lin; Xihao Li; Jane A. Driver; Liming Liang (Human Genetics, 2019)

HOTAIR functions as a competing endogenous RNA to regulate PTEN expression by inhibiting miR-19 in cardiac hypertrophy - Yanjun Lai; Shuai He; Liming Ma; Hong Lin; Biyun Ren; Jing Ma; Xinyu Zhu; Shifang Zhuang (Molecular and Cellular Biochemistry, 2017)

RETRACTED ARTICLE: Role of Glibenclamide in Brain Injury After Intracerebral Hemorrhage - Bing Jiang; Lin Li; Qianwei Chen; Yihao Tao; Liming Yang; Bo Zhang; John H. Zhang; Hua Feng; Zhi Chen; Jun Tang; Gang Zhu (Translational Stroke Research, 2017)

Glacier elevation changes (2012–2016) of the Puruogangri Ice Field on the Tibetan Plateau derived from bi-temporal TanDEM-X InSAR data - Lin Liu; Liming Jiang; Yafei Sun; Chaolu Yi; Hansheng Wang; Houtse Hsu (International Journal of Remote Sensing, 2016)

Minocycline Attenuates Neonatal Germinal-Matrix-Hemorrhage-Induced Neuroinflammation and Brain Edema by Activating Cannabinoid Receptor 2 - Jun Tang; Qianwei Chen; Jing Guo; Liming Yang; Yihao Tao; Lin Li; Hongping Miao; Hua Feng; Zhi Chen; Gang Zhu (Molecular Neurobiology, 2016)

Comprehensive analysis of tropomyosin isoforms in skeletal muscles by top-down proteomics - Yutong Jin; Ying Peng; Ziqing Lin; Yi-Chen Chen; Liming Wei; Timothy A. Hacker; Lars Larsson; Ying Ge (Journal of Muscle Research and Cell Motility, 2016)

A Cannabinoid Receptor 2 Agonist Prevents Thrombin-Induced Blood–Brain Barrier Damage via the Inhibition of Microglial Activation and Matrix Metalloproteinase Expression in Rats - Lin Li; Yihao Tao; Jun Tang; Qianwei Chen; Yang Yang; Zhou Feng; Yujie Chen; Liming Yang; Yunfeng Yang; Gang Zhu; Hua Feng; Zhi Chen (Translational Stroke Research, 2015)

Transcriptome analysis reveals dynamic changes in the gene expression of tobacco seedlings under low potassium stress - LIMING LU; YONG CHEN; LIN LU; YIFEI LU; LIQIN LI (Journal of Genetics, 2015)

Vascular smooth muscle cell differentiation to an osteogenic phenotype involves matrix metalloproteinase-2 modulation by homocysteine - Tingjiao Liu; Jinghan Lin; Ting Ju; Lei Chu; Liming Zhang (Molecular and Cellular Biochemistry, 2015)

Identifying and managing risk factors for salt-affected soils: a case study in a semi-arid region in China - De Zhou; Jianchun Xu; Li Wang; Zhulu Lin; Liming Liu (Environmental Monitoring and Assessment, 2015)

Development of quantification bioassays for live propagules of Phytophthora sojae in soil - Bing Suo; Caixia Xiao; Haocheng Lin; Qiuming Chen; Liming Zhao; Miao Tian; Qianqian Sun; Jingzhi Wen (Journal of General Plant Pathology, 2015)

Protective effect of berberine against myocardial ischemia reperfusion injury: role of Notch1/Hes1-PTEN/Akt signaling - Liming Yu; Feijiang Li; Guolong Zhao; Yang Yang; Zhenxiao Jin; Mengen Zhai; Wenjun Yu; Lin Zhao; Wensheng Chen; Weixun Duan; Shiqiang Yu (Apoptosis, 2015)

Intracellular Ca2+ Overload Induced by Extracellular Ca2+ Entry Plays an Important Role in Acute Heart Dysfunction by Tentacle Extract from the Jellyfish Cyanea capillata - Lin Zhang; Qian He; Qianqian Wang; Bo Zhang; Beilei Wang; Feng Xu; Tao Wang; Liang Xiao; Liming Zhang (Cardiovascular Toxicology, 2014)

Development of a multiplex TaqMan real-time RT-PCR assay for simultaneous detection of Asian prunus viruses, plum bark necrosis stem pitting associated virus, and peach latent mosaic viroid - Liming Lin; Ruhui Li; Margarita Bateman; Raymond Mock; Gary Kinard (European Journal of Plant Pathology, 2013)

Alkanes, compound-specific carbon isotope measures and climate variation during the last millennium from varved sediments of Lake Xiaolongwan, northeast China - Qing Sun; Manman Xie; Liming Shi; Zhuyue Zhang; Yuan Lin; Wenyu Shang; Kaijun Wang; Wei Li; Jiaqi Liu; Guoqiang Chu (Journal of Paleolimnology, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

One-step multiplex RT-PCR for simultaneous detection of four pome tree viroids - Liming Lin; Ruhui Li; Ray Mock; Gary Kinard (European Journal of Plant Pathology, 2012)

A Common variant near the melanocortin 4 receptor is associated with low-density lipoprotein cholesterol and total cholesterol in the Chinese Han population - Liming Tao; Zhou Zhang; Zhuo Chen; Daizhan Zhou; Weidong Li; Mengyuan Kan; Di Zhang; Lin He; Guoying Huang; Yun Liu (Molecular Biology Reports, 2012)

A Novel Canine Model of Portal Vein Stenosis Plus Thioacetamide Administration-Induced Cirrhotic Portal Hypertension With Hypersplenism - Dexin Lin; Xianbin Wu; Xiaoke Ji; Qiyu Zhang; YuanWei Lin; WeiJian Chen; Wangxun Jin; Liming Deng; Yunzhi Chen; Bicheng Chen; Jianmin Li (Cell Biochemistry and Biophysics, 2012)

Increasing water and nitrogen availability enhanced net ecosystem CO2 assimilation of a temperate semiarid steppe - Liming Yan; Shiping Chen; Jianhui Huang; Guanghui Lin (Plant and Soil, 2011)

Monitoring and assessing reclamation settlement in coastal areas with advanced InSAR techniques: Macao city (China) case study - Liming Jiang; Hui Lin; Shilai Cheng (International Journal of Remote Sensing, 2011)

Candida tropicalis: characterization of a strain capable of degrading high concentrations of phenol - Liming Wang; Yanwen Lin; Linyan Yang; Ping Yu; Zhixiong Xie; Yunbai Luo (Biotechnology Letters, 2011)

Differential responses of auto‐ and heterotrophic soil respiration to water and nitrogen addition in a semiarid temperate steppe - LIMING YAN; SHIPING CHEN; JIANHUI HUANG; GUANGHUI LIN (Global Change Biology, 2010)
Evaluating how autotrophic (SR A ), heterotrophic (SR H ) and total soil respiration (SR TOT ) respond differently to changes of environmental factors is critical to get an understanding of ecosystem carbon (C) cycling and its feedback processes to climate change. A field experiment was conducted to examine the responses of SR A and SR H to water and nitrogen (N) addition in a temperate steppe in northern China during two hydrologically contrasting growing seasons. Water addition stimulated SR A and SR H in both years, and their increases were significantly greater in a dry year (2007) than in a wet year (2006). N addition increased SR A in 2006 but not in 2007, while it decreased SR H in both years, leading to a positive response of SR TOT in 2006 but a negative one in 2007. The different responses of SR A and SR H indicate that it will be uncertain to predict soil C storage if SR TOT is used instead of SR H to estimate variations in soil C storage. Overall, N addition is likely to enhance soil C storage, while the impacts of water addition are determined by its relative effects on carbon input (plant growth) and SR H . Antecedent water conditions played an important role in controlling responses of SR A , SR H and the consequent SR TOT to water and N addition. Our findings highlight the predominance of hydrological conditions in regulating the responses of C cycling to global change in the semiarid temperate steppe of northern China.

Synergistic use of optical and InSAR data for urban impervious surface mapping: a case study in Hong Kong - Liming Jiang; Mingsheng Liao; Hui Lin; Limin Yang (International Journal of Remote Sensing, 2009)

Effect of burn injury on apoptosis and expression of apoptosis-related genes/proteins in skeletal muscles of rats - Hongjie Duan; Jiake Chai; Zhiyong Sheng; Yongming Yao; Huinan Yin; Liming Liang; Chuanan Shen; Jing Lin (Apoptosis, 2009)